Crossing the borders of justice : a philosophical study of climate change, justice and environment - Lipponen, Nea Emilia (2011)
This thesis studies climate change as a problem of justice from the point of view of political philosophy, especially the distributive model of social justice. The main problem is to examine what justice in the context of climate change means and how it differs from and challenges the traditional ways of conceptualizing justice in terms of distribution. The main argument is that climate change is not simply a problem to be redressed by getting distributive aspects right, and in order to move on from remedial approaches towards preventing further damage it is necessary to discuss the issue in terms of refraining from harming. Climate change is understood in this thesis as fundamentally a question of justice. Justice in this context requires not only fairer allocation of shares of atmospheric capacity to absorb emissions and more generally of ecological space, but also shifting focus to the structures that maintain and reproduce the inequalities in access to environmental goods and distribution of burdens related to climate change. Also participation, which pertains to the domain of procedural justice, of the most vulnerable and powerless people and countries is a crucial aspect of climate justice. Climate change has catalyzed diverse claims and conceptualizations of justice, which reflects the condition of radical heterogenization of justice discourse. A climate treaty cannot address all these legitimate concerns, but this should not be confused with the idea that we should level down the claims of justice. While the idea of compensation of climate related damages is not entirely rejected, critical points about the possibility of compensating environmental goods such as atmospheric commons are raised. Compensatory justice has the same problem as distributive justice: it cannot create more of the depleted resource that is actually needed more than monetary compensation or substitute. In the discussion of the implications of scarcity on distribution and climate politics, the limitations of the ideas of distribution (as it is usually understood) and compensation become even more evident. This thesis examines climate change as a form of doing harm. This is a relatively novel approach to climate change and justice, because usually the debates revolve around the distributive aspects and not on normative analysis of the actions that contribute to climate change itself. The viewpoint of harm opens new possibilities to examine justice in climate change.